Gear Type Transfer Pump for Palm Sugar Production's Engine by Evaporation Method - Sunarno, Sunarno; Nuradi, Nuradi; Prihartono, Joko (International Journal Labs, 2023)
Along with the times, the process of managing palm sugar has been developed based on the large scale and how efficient the management process is, in this case the method used is evaporation where the sap is circulated several times for the process of draining the water in the Economizer, for the circulation process there is a pump to be able to accelerating the flow system so that the traditional process continues until the sap becomes half the process (thick sap). For this reason, a gear type pump is used so that it can move fluids with high viscosity. In this case the pump used with maximum specifications, the effective head of the pump installation is 52.1573 ???? and a capacity of 0.001 ????³/s, and the theoretical pump power is 0.098 ????????, while the resulting shaft power is 0.14 ????????, the motor has a power of 0.147 kW . As well as the type of External Gear Pump selected with a rotation of 400 rpm and a power of 0.14 kW.